2010
DOI: 10.1016/j.bone.2009.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids, osteocytes, and skeletal fragility: The role of bone vascularity

Abstract: Glucocorticoid administration is required for many inflammatory and autoimmune diseases, but use of these drugs is associated with skeletal side effects including bone loss, fractures, and osteonecrosis. Fractures often occur without a reduction in bone mineral density, strongly suggesting that glucocorticoid excess adversely affects other aspects of bone strength. Although the primary effects of glucocorticoid excess on the skeleton are directly on bone cells, a vascular connection between these cells and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 49 publications
7
88
0
2
Order By: Relevance
“…Glucocorticoids also decrease intestinal calcium absorption thus further predisposing to osteoporosis. Recently, effects of glucocorticoids on decreasing bone vasculature, has also been implicated as a potential mechanism for glucocorticoid effects on bone [126]. There also seems to be an agedependence of glucocorticoid effects on bone.…”
Section: Mechanismmentioning
confidence: 99%
“…Glucocorticoids also decrease intestinal calcium absorption thus further predisposing to osteoporosis. Recently, effects of glucocorticoids on decreasing bone vasculature, has also been implicated as a potential mechanism for glucocorticoid effects on bone [126]. There also seems to be an agedependence of glucocorticoid effects on bone.…”
Section: Mechanismmentioning
confidence: 99%
“…During aging or glucocorticoid treatment, bone angiogenesis is reduced and brittleness in bone is increased (Weinstein, 2010;Weinstein et al, 2010). VegfA overexpression in bone marrow leads to formation of new bone and associated blood vessels (Maes et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that glucocorticoidinduced fractures tend to be multiple and occur at BMD values that are higher than in patients with other kinds of osteoporosis. The adverse effects on bone of excess glucocorticoid may, therefore, be partly due to abnormalities that are not related to the decline in bone mass [ 121,176 ] .…”
Section: Glucocorticoids and Osteoporosismentioning
confidence: 98%
“…Within the fi rst year, BMD is reduced by 6-12% and by about 3% in each subsequent year of additional treatment. The relative risk of fracture escalates by as much as 75% within the fi rst 3 months after initiation of steroid therapy [ 163,176 ] . Up to 50% of patients develop vertebral fractures if under prolonged treatment with systemic glucocorticoids [ 27,41,50,115 ] .…”
Section: Glucocorticoids and Osteoporosismentioning
confidence: 99%